EARLY JURASSIC (SINEMURIAN TO BASAL TOARCIAN) AMMONITES OF THE BRESCIAN PREALPS (SOUTHERN ALPS, ITALY) - CHRISTIAN MEISTER; PAOLO SCHIROLLI; JEAN-LOUIS DOMMERGUES (Rivista Italiana di Paleontologia e Stratigrafia, 2017)
This work provides a more precise up-to-date biostratigraphical framework of the Early Jurassic ammonite succession of the Brescian Prealps with more than seventy taxa for the Sinemurian, Pliensbachian and basal Toarcian corresponding to a about 30 horizons or faunal assemblages rather well correlable with the NW European standard zonation. These results are supported with already published data, new data from recent field investigations, revised contributions of different authors and with the study of the historical collection of the Museum of Natural Sciences of Brescia (Northern Italy). The biohorizons are referred to the Lower Jurassic carbonate series of the Brescian Prealps, cropping out between the eastern surroundings of Brescia (Botticino-Serle), to the East, and the Lake Iseo, to the West. This area was located in the eastern border of the wide Lombardian Basin, a part of the southern continental passive margin subjected to the Jurassic rifting, preceding the Neo-Tethys opening.